Implications of the presence of an emergency medicine pharmacist during critical care trauma patient resuscitation. Issue 3 (4th January 2019) - Lamkin, Lynn; Lindsey, Savannah; Weant, Kyle; Shoff, Hugh; Pinkston, Christina
Abstract : Purpose: The available literature has shown that the presence of an Emergency Medicine Pharmacist (EMP) is associated with decreased time to medication procurement, a reduction in medication errors, and overall cost avoidance. However, there is limited literature that systematically evaluates the impact of EMPs in the treatment of critically ill trauma patients presenting to the emergency department (ED). Methods: This study was a retrospective chart review evaluating 1082 adult patients presenting to the critical care area (CCA) of the ED at the University of Louisville Hospital in Louisville, Kentucky for trauma evaluation from July 2014 to December 2014. The study group consisted of patients presenting to the CCA when an EMP was present. Primary outcomes included time to administration of antibiotics, analgesia medication, sedation medication, rapid sequence intubation (RSI), and anticoagulation reversal. Secondary outcomes included time to administration of appropriate antibiotics at an appropriate dose and vaccination administration. Results: The presence of an EMP was associated with a statistically significant decreased median time from triage to the administration of an analgesic medication (11 minutes [interquartile range (IQR) 8‐27] vs 13 minutes [IQR 8.5‐20], P  = 0.04). There was no statistically significant difference in triage time to antibiotic administration, RSI, sedation medication administration, or anticoagulation reversal. Patients in the EMP group were more likely to receive appropriate empiric antibiotics compared with the control group (80.7% vs 52.2%, P  = 0.01). Conclusion: The presence of an EMP was associated with decreased time to analgesia medication administration as well as an increased likelihood of the administration of appropriate empiric antibiotics in critically ill trauma patients.